2005
DOI: 10.1038/sj.ijo.0802891
|View full text |Cite
|
Sign up to set email alerts
|

Long-period accelerometer monitoring shows the role of physical activity in overweight and obesity

Abstract: CONTEXT: Physical activity (PA) plays an important role in obesity. A new accelerometer has been developed to assess total energy expenditure as well as PA. OBJECTIVE: To investigate the association of PA with overweight and obesity in Japanese men and women, a large crosssectional study was performed using a single-axis accelerometer. DESIGN, SETTING AND PARTICIPANTS: Population-based cross-sectional study of Japanese 18-84 y of age. Height, body weight and PA were measured in 400 male and 388 female Japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 34 publications
10
54
0
Order By: Relevance
“…These proportions are close to those recently reported in other studies that used accelerometry in healthy young adults (7,35). McClain et al (20), on the other hand, recruited regular endurance runners and although %Moderate was similar in their study (27 min/ day), %High was more pronounced (48 min/day) compared with the present population.…”
Section: Discussionsupporting
confidence: 36%
“…These proportions are close to those recently reported in other studies that used accelerometry in healthy young adults (7,35). McClain et al (20), on the other hand, recruited regular endurance runners and although %Moderate was similar in their study (27 min/ day), %High was more pronounced (48 min/day) compared with the present population.…”
Section: Discussionsupporting
confidence: 36%
“…Several population-based studies found a cross-sectional association between higher levels of self-reported physical activity and lower BMI (13)(14)(15)(16). Research further suggests that time spent performing vigorous aerobic activities may be especially important for reducing the likelihood of being overweight or obese (15,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…This higher energy expenditure can be explained by the signiˆcantly higher resting metabolic rates in obese individuals as compared with those in normal-weight individuals (Riggs et al, 2007). Obese individuals also carry a heavier load, which requires more energy and therefore their energy expenditure may be higher (Yoshioka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%